The Nucleon Optical Model - Hodgson P.E. (World Scientific, 1994)
The nucleon optical model is widely used to calculate the elastic scattering cross-sections and polarizations for the interaction of neutrons and protons with atomic nuclei. The optical model potentials describe not only the scattering but also provide the wave functions needed to analyze a wide range of nuclear reactions. They also unify many aspects of nuclear reactions and nuclear structure. This book describes the optical model in detail, with full references to the original literature and many examples of its application to analyze experimental data.